2013 23rd International Conference on Field Programmable Logic and Applications 2013
DOI: 10.1109/fpl.2013.6645523
|View full text |Cite
|
Sign up to set email alerts
|

Run-time optimization of a dynamically reconfigurable embedded system through performance prediction

Abstract: A key tool to increase the exploitation of dynamic reconfigurable platforms is the run-time resource manager. This system module coordinates the usage of both software and reconfigurable hardware resources in the context of a multi-programmed environment, by alleviating the operating system's induced overhead. This paper introduces a two-layers run-time resource manager for dynamic reconfigurable platforms. The upper level is composed of several application-level managers (one for each application) that provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The closest published research to our work can be found in [19], [20], [21] and [22]. In [19], the authors presents a high level prediction modeling technique that produces prediction models for is cellaneous platforms and tool chains and application domains.…”
Section: Supervised Learning Stepsmentioning
confidence: 99%
See 1 more Smart Citation
“…The closest published research to our work can be found in [19], [20], [21] and [22]. In [19], the authors presents a high level prediction modeling technique that produces prediction models for is cellaneous platforms and tool chains and application domains.…”
Section: Supervised Learning Stepsmentioning
confidence: 99%
“…The work in [20] presents a framework consisting of two layers for resource management of dynamic reconfigurable platforms. The proposed system is capable of evaluating the performance of a reconfigurable computing platform based on prediction model.…”
Section: Supervised Learning Stepsmentioning
confidence: 99%